Study of stress and strain state distribution of spinal model in surgical techniques for various techniques for thoracolumbar burst fractures (part two) - Radchenko, Volodymyr; Popsuishapka, Kostiantin; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
When choosing the tactics of surgical treatment in burst fractures of the lower thoracic and lumbar spine, the questions remain about the extent of fixation, the possibility of correcting the deformity, and the feasibility of performing a laminectomy. Objective: to construct finite-element biomechanical models of an burst fracture of the ThXII vertebral body with 100 % lesion in the ThIX–LVvertebra block and analyze the stress-strain state with different types of fixation. Methods: four models of the ThIX–LVvertebra block were developed: 1) replacement of the fractured vertebral body with an interbody support, destruction of vertebral arches and fixation of vertebrae ThX, ThXI, LI, LIIt ranspedicular c onstruction; 2 ) d estruction o f 100 % of the volume of the vertebral body ThXIIand fixation of the vertebrae ThX, ThXI, LI, LIItranspedicular construction; 3) replacement of the destroyed vertebra by an interbody support, destruction of arches of vertebra ThXIIand fixation of vertebrae ThXI and LI transpedicular construction; 4) replacement of the destroyed vertebra by an interbody support. Results: it was established that transpedicular construction bears the main load, maximum stresses were found in the posterior parts of the spine (up to 6 MPa) and the sections of the rods between the vertebrae (36.9–65.7 MPa, depending on the model). When using 8 screws without an interbody support for fixation, the stress level increased significantly: in the «screw – bone» region more than 2 times, in the rods — by 70 %. In the case of using 4 screws, the level of stress in the area of the posterior support complex averaged 10–40 % on average. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> in vertebral blocks the most strained are the posterior parts of the spine and the portions of the rods between vertebras. The use of a 360° fusion increases the load in the «screw – bone» zone, and only the interbody support — in the region of the posterior parts of the spine.